PLANT-BASED FERMENTED FOODS: A REVIEW OF MICROBIOLOGICAL, BIOCHEMICAL, AND SENSORY PROPERTIES (The Research of Medical Science Review, 2025)
Plant-based fermented foods have gained increasing attention due to their health benefits, enhanced nutritional value, and improved sensory properties. Fermentation plays a crucial role in modifying the biochemical composition of plant-based foods, leading to the production of bioactive compounds, improved digestibility, and the reduction of antinutritional factors. The microbiological aspect of fermentation is essential, as diverse microorganisms, including lactic acid bacteria, yeasts, and molds, contribute to flavor development, texture modification, and extended shelf life. These microbial interactions lead to complex biochemical changes, including the breakdown of macronutrients, the synthesis of vitamins and antioxidants, and the formation of unique flavor compounds. Sensory attributes such as taste, aroma, texture, and color are significantly influenced by fermentation, affecting consumer acceptability. Despite these advantages, challenges such as standardization, safety concerns, and variability in fermentation processes limit the large-scale application of plant-based fermented foods. Additionally, there is a need for further research on optimizing fermentation conditions, ensuring probiotic viability, and enhancing functional properties. Future advancements should focus on integrating biotechnology, improving microbial strains, and developing innovative fermentation techniques to create sustainable and nutritionally superior plant-based products. This review highlights the microbiological, biochemical, and sensory aspects of plant-based fermented foods while identifying research gaps and potential areas for future innovation.